(untitled) - Corréard, Marie-Hélène (Oxford, 1994)
This French-English dictionary is the result of a collaboration between two of the world's foremost reference-book publishers. It features authoritative comments and a comprehensive up-to-date vocabulary.
Keywords: French language,English language